Effect of the patatin‐like phospholipase domain containing 3 gene (PNPLA3) I148M polymorphism on the risk and severity of nonalcoholic fatty liver disease and metabolic syndromes: A meta‐analysis of paediatric and adolescent individuals. Issue 6 (5th February 2020) - Li, Jiaying; Hua, Wenxi; Ji, Cheng; Rui, Jingwen; Zhao, Yuening; Xie, Chenyao; Shi, Bimin; Yang, Xiaoqin
Summary: Background: The effect of the patatin‐like phospholipase domain containing 3 gene ( PNPLA3 ) I148M polymorphism on the risk and severity of paediatric and adolescent nonalcoholic fatty liver disease (NAFLD) remains inconclusive. Objectives: We aimed to estimate the effect of this polymorphism not only on early‐onset NAFLD risk and severity but also on metabolic syndromes susceptibility. Methods: A systematic literature search was performed to identify relevant datasets. The odds ratio of the dichotomic variables and the standardized mean difference of quantitative variables with corresponding 95% confidence intervals were calculated to assess the strength of the associations. Results: Twenty‐seven studies comprising 10 070 subjects were eligible. The summary effect showed that this polymorphism increased susceptibility to NAFLD development. Furthermore, it also indicated that nonalcoholic steatohepatitis (NASH) was more frequently observed in G allele carriers among paediatric and adolescent NAFLD patients. Moreover, the meta‐analysis suggested that the variant was significantly associated with elevated liver damage indexes, including serum alanine transaminase, aspartate transaminase, gamma‐glutamyltransferase concentrations, and liver fat content. However, the summary estimates for insulin resistance, lipid metabolism, and adiposity showed no significant associations. Conclusions: The PNPLA3 I148M polymorphism is associated with elevated early‐onset NAFLD risk, severity, and liver damage but not with related metabolic syndromes.